PENGARUH PENGINTEGRASIAN MIND MAPPING KE DALAM MODEL INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN PEMAHAMAN KONSEP EKOLOGI PADA SISWA KELAS X SMA MUHAMMADIYAH 1 PEKANBARU - Aulia Winnas; Yuslim Fauziah; Fitra Suzanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research has been conducted at Muhammadiyah 1 High School in Pekanbaru in May 2018 which aims to determine the effect of integrating mind mapping into a guided inquiry model on creative thinking skills and understanding of ecological concepts in class X Muhammadiyah 1 high school seniors. This type of research is a quasi-experimental study with a randomized control group pretest-posttest research design. The sample consisted of two classes, namely class X MIA1 as experimental class and class X MIA2 as control class randomly selected after normality and homogeneity tests. The experimental class is the class applied guided inquiry learning model by integrating mind mapping while the control class is not treated. The data analysis technique used is the t test. Based on the data analysis test obtained tcount> t table t count> t table (3.07> 1.67), meaning that the application using a guided inquiry model can improve students' creative thinking abilities and tcount> t table (3.88> 1.67), tcount> ttable (3.88> 1.67), using the Guided Inquiry Model can improve the Understanding of Concepts for Class X Students of Muhammadiyah 1 High School Pekanbaru. The categories of students' creative thinking abilities are low with (N-gain = 0.24) and the conceptual understanding category of students is moderate (N-gain = 0.52).Key Words: Guided Inquiry Model, Mind Mapping, Creative Thinking Ability, Concept Understanding